Perceptions of Peer Tutoring at a University in Chile - Silvina Silvina Zapata (Pontificia Universidad Javeriana, 2020)
The purpose of this Action Research study is to explore students' perceptions of their experience in an Academic Support Program* (ASP) implemented in a Chilean university to align students' lack of competencies to the minimum required to be able to succeed. Focus groups were held with 21 participants who revealed that the ASP increased their self-confidence and academic achievement. However, students' level of awareness regarding the benefits of the ASP needs to be improved to promote their participation. The findings will generate an action plan to improve students' learning outcomes and well-being.